Effect of prior oxidation and creep damages on subsequent tensile properties of low alloy steels. (27th September 2019) - Wang, Hang; Yang, Shangyu; Han, Lihong; Yu, Shouming; Ren, Shuai; Zhang, Guojun
Abstract: Low alloy steels find extensive use in thermal recovery well oil casing, while the degradation on tensile properties is ineluctable operating at high temperature. So this study focuses on evaluating the effect of prior oxidation and creep damages on subsequent tensile properties of C–Mn steel and 3Cr–Mo steel. Prior oxidation tests interrupted at different time are conducted at 450 °C, 600 °C and 800 °C, respectively. And prior creep tests interrupted at different time are implemented at 600 °C and 400 MPa. Then subsequent tensile tests are carried out at room temperature. Results indicate that the remnant tensile strength (RTS) of 3Cr–Mo steel changes slightly after prior oxidation or creep tests at 600 °C, while that of C–Mn steel decreases significantly. As prior oxidation temperature increases to 800 °C, the RTS of both steels presents dramatic deterioration. Moreover, the remnant elastic modulus of C–Mn steel and 3Cr–Mo steel exhibit no significant changes after prior oxidation or creep at 600 °C, while show sharp decline after prior oxidation at 800 °C. Microstructure observations reveal that the deterioration of remnant tensile properties is mainly attributed to the microstructure instability such as coalescence and coarsening of carbides. Besides, oxide film cracking or peeling may also promote the decline of RTS.